Pengaruh Anime dan Manga terhadap Motivasi Belajar Mahasiswa Sastra Jepang di Universitas Nasional PASIM - Chinta Ramadani; Khairun Nisa Hermawati; Melani Nurfathia Ardian; Sri Mulyeni (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to examine the impact of anime and manga on increasing the learning motivation of students in the Japanese Literature Study Program at Universitas Nasional PASIM. As elements of modern Japanese popular culture, anime and manga function not only as a form of entertainment media but also as sources that can foster students’ interest in the Japanese language and culture. The rapid advancement of technology and the increasing ease of access to anime and manga through various digital platforms have making them an integral part of students’ daily lives, making their impact on education an important topic of study. This study employed a quantitative research method using a survey approach. This study gathered data through questionnaires completed by 33 students enrolled in the Japanese Literature program. Due to the relatively small population size, a total sampling technique was applied, involving all members of the population in the study. The data obtained were analyzed through validity, reliability, and normality tests, as well as the coefficient of determination, to assess the appropriateness of the research instruments and to examine the influence of anime and manga on students’ learning motivation. The analysis demonstrates that the indicators for anime and manga as well as learning motivation have fulfilled validity and reliability requirements, suggesting that the instruments are appropriate for application. A coefficient of determination of 55.1% indicates that anime and manga have a substantial contribution to students’ learning motivation, while the remaining proportion is affected by other variables not addressed in this research. These results suggest that anime and manga function not only as forms of entertainment but also as supportive learning media capable of enhancing the learning motivation of Japanese Literature students.